Student Engagement dalam Kegiatan Intrakurikuler pada Peserta Didik di SMAN Keberbakatan Olahraga Flobamorata Kupang - Nasri, Maria Velixita; Saba, Khetye Romelya; Febriana, Febriana (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Student engagement refers to the active involvement of students in the learning process, encompassing behavioral, emotional, and cognitive aspects. In reality, not all students demonstrate optimal engagement, particularly in sports-based schools where they must divide their focus between academics and physical training. This study aims to describe the level of student engagement among students of SMAN Keberbakatan Olahraga Flobamorata Kupang. This research employed a quantitative approach with a descriptive design. The population and sample consisted of 144 students, determined through saturated sampling. Data were collected using a Likert-scale questionnaire. The findings revealed that most students demonstrated a high level of student engagement, with 75 students (52%) categorized as high. In terms of behavioral engagement, 68 students (47%) were in the moderate category. Emotional engagement was predominantly high with 72 students (50%), while cognitive engagement was also largely high with 67 students (47%). It can be concluded that students generally demonstrate optimal engagement in intracurricular activities despite carrying dual roles as learners and athletes. The implication is that schools should implement interactive and varied learning methods to sustain and enhance student engagement, particularly in behavioral aspects. The limitations of this study include the timing of questionnaire administration coinciding with training schedules, the use of a try-out within the actual sample, and the absence of a reference period of events in the questionnaire.student engagement